Physiological characteristics of a promising black locust (Robinia pseudoacacia L.) clone under marginal site conditions - Ábri, Tamás (Acta Agraria Debreceniensis, 2025)
This paper studies the physiological characteristics of a promising black locust (Robinia pseudoacacia L.) clone, Farkasszigeti, compared to common black locust (control), under marginal site conditions in Eastern Hungary. A clone trial was established in 2022 near Debrecen to test new black locust clones, with measurements of photosynthesis (net assimilation, efficiency of photosystem II, intercellular CO2 level) and water-use characteristics (transpiration, stomatal conductance, water use efficiency etc.), using LI-6800 (LI-COR) portable photosynthesis system. However, the measured values were very low, indicating drought and heat stress. The results revealed that Farkasszigeti exhibited better net assimilation (2.13±0.75 µmol CO2 m-2 s-1), transpiration (1.41±0.20 mmol H2O m-2 s-1) and stomatal conductance (0.017±0.002 mol m-2 s-1) than the control, with significant differences (p=0.05). Furthermore, its photosystem II was more efficient, thus it has better heat tolerance. Although the clone Farkasszigeti was proved to be better in terms of water use efficiency values, no significant difference was observed in comparison with the control common black locust. Today, under changing climatic conditions, the study of physiological adaptation of tree species and clones has a crucial role.